OPTIMAL USING PORTFOLIO DIVERSIFICATION MULTI AGENT METHOD IN THE CAPITAL MARKET - Asri Jaya; Fitri Handayani Alnur; Muchriana Muchran (Magister Akuntansi, Universitas Atma Jaya Makassar, 2023)
This study aims to apply the multi agent method in order to help investorspredict stock prices by reducing risk when investing. This is based on the behaviorof investors when making decisions in investing in the capital market in consideringthe risks that my occur if they do not manage their portpolios properly. It is knowthat there are 3 papular indicators associated with the multi agent method namelySMA, RSI, dan BB which are used to find out recommendations for stocks to beinvested. Based on the multi agent method, with a population of shares listed inthe LQ-45 index in the period 2019 tp 2021, and sample selection using thepurposive sampling by obtaining 38 samples of stocks with secondary dataobtained from stocks that consistently always exist in the LQ-45 index in the studyperiod totaling 12 samples. The results of the study indicate that there are 3 stocksthat have good portpolios and are also not good for investment. The 3 shares,namely BTPS, BBTN have recommended shares for sale. While ADRO has goodstock recommendations to buy and can be proven by opening tha profitsapplication so that the final results made are real and can be proven.